PENGARUH LINGKUNGAN KERJA DAN KARAKTERISTIK INDIVIDU TERHADAP KINERJA KARYAWAN BANK SYARIAH INDONESIA (BSI) CABANG ULEE KARENG BANDA ACEH - Nurbismi Nurbismi; Yasmin Syaza (SI-MEN, 2022)
The purpose of this study was to determine the effect of the work environment and individual characteristics on employee performance at Bank Syariah Indonesia (BSI) Ulee Kareng Branch Banda Aceh. To reveal the problem in depth and comprehensively, the researcher used a quantitative method with a total sampling technique in the form of a questionnaire distributed to 30 respondents. The data analysis technique used is multiple linear regression using the SPSS program. Then the data is described, analyzed, and discussed to answer the problems posed. From the results of this study, there is a significant effect of the work environment and individual characteristics on employee performance at Bank Syariah Indonesia (BSI) Ulee Kareng Branch Banda Aceh with significant results at 0.031<α= 0.05 and 0.000<α=0.05, with the percentage 0.640 or 64%.